KAJIAN PUSTAKA TENTANG HUKUM ADAT SEBAGAI SUMBER HUKUM TIDAK TERTULIS DAN PENGARUHNYA TERHADAP TATA NILAI SOSIAL - Rengga Yudha Santoso; Dea Valentina (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to analyze the existence of customary law as an unwritten legal source and its influence on the social value system within Indonesian society. Using a qualitative approach and a systematic literature review design, this research identifies and reviews Scopus-indexed and reputable scholarly literature discussing living law, legal pluralism, and social norms embedded in customary communities. The findings reveal that customary law functions as a living law rooted in cultural values and collective beliefs, playing a significant role in shaping social norms, maintaining harmony, and strengthening community cohesion. Compliance with customary law is moral and social in nature, driven by collective awareness and cultural legitimacy rather than formal sanctions. Furthermore, customary law embodies social values such as mutual cooperation, deliberation, and communal justice, serving as the moral foundation of society. However, its existence faces challenges from the dominance of positive law and modernization; thus, a legal pluralism approach is needed to acknowledge normative diversity and integrate customary law into the national legal system. This study emphasizes the importance of recognizing customary law within national legal policy to build an inclusive, contextual, and socially just legal system.